Pengaruh Pelatihan Terhadap Kinerja Karyawan Pada PT. Cipta Sejati Revolution Makassar - Bandhaso, Mira Labi; Tandirerung, Jeane; Sasabone, Luana (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2023)
This research aims to determine the effect of training on employee performance at PT.Cipta Sejati Revolution. This research was conducted at PT Cipta Sejati Revolution which operates in the field of outsourcing labor distribution located in the city of Makassar. The population of this research is the entire number of employees who work at PT.Cipta Sejati Revolution, totaling 30 employees. So, the researcher took the entire population to be used as a sample, namely 30 people. This research design uses quantitative methods to determine the relationship between two variables, namely training (x) and employee performance (y) using SPSS consisting of the Spearman Rank correlation coefficient, coefficient of determination, and t test results. From the research results it was found that training (X) had a positive and significant effect on employee performance at PT. Cipta Sejati Revolution.